Innovative approaches in wound healing: trajectory and advances. (June 2013) - Singh, Manju Rawat; Saraf, Shailendra; Vyas, Amber; Jain, Vishal; Singh, Deependra
Abstract Wound is one of the oldest suffering associated with the mankind and its history is as old as humanity. Advances in the field of medical sciences created a pile of knowledge and paved the path for the development of a separate branch specifically devoted for wound healing. The understanding and treatment strategies for wound healing have gone through a great revolution. This article reviews all the aspects of wound healing including the pathway, types and recent advances made in the wound care management in particular moist wound dressings using natural polymers, skin grafts, debridement, growth factor and drug delivery.